Edible films and coatings containing bioactives - Salgado, Pablo Rodrigo (2015)
Edible films and coatings are promising systems to be used as active ingredient carriers. As they can be consider both a packaging and a food component, they have to fulfill specific requirements: good sensory attributes, high barrier and mechanical properties, biochemical, physicochemical, and microbial stability, safety, non-polluting nature, simple technology and low raw material and processing cost. The addition of bioactive compounds and additives contributes to achieve these requirements to preserve the quality, safety and sensory properties of foods. Research efforts are focused in attempting to optimize the composition of film and coatings materials in order to be well-processed and effective in real, pragmatic, everyday food systems. This short review attempts to summarize the current state of knowledge on this subject, including general aspects, new trends and some successful applications.